2015
DOI: 10.1002/aenm.201501728
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pillar Height and Junction Depth on the Performance of Radially Doped Silicon Pillar Arrays for Solar Energy Applications

Abstract: The effects of pillar height and junction depth on solar cell characteristics are investigated to provide design rules for arrays of such pillars in solar energy applications. Radially doped silicon pillar arrays are fabricated by deep reactive ion etching of silicon substrates followed by the introduction of dopant atoms by diffusion from a phosphorus oxide layer conformally deposited by low‐pressure chemical vapor deposition. Increasing the height of the pillars has led to doubling of the efficiency from 6% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…Silicon nano/micro-engineering process flows have enabled the fabrication of more complex structured silicon solar cells, and in particular the development of 3D micropillar structures with radial p/n junctions. [5][6][7][8] The efficiencies of these silicon micropillar arrays depend on various parameters. In our previous work an optimum was found for pillars with a length of 40 µm and a junction depth of close to 1 µm.…”
Section: Doi: 101002/aenm201601497mentioning
confidence: 99%
“…Silicon nano/micro-engineering process flows have enabled the fabrication of more complex structured silicon solar cells, and in particular the development of 3D micropillar structures with radial p/n junctions. [5][6][7][8] The efficiencies of these silicon micropillar arrays depend on various parameters. In our previous work an optimum was found for pillars with a length of 40 µm and a junction depth of close to 1 µm.…”
Section: Doi: 101002/aenm201601497mentioning
confidence: 99%
“…Nanowires based solar cell in the field of fabrication technique and materials properties were studied a lot; however, numerical simulations were rarely reported [10,11]. Based on efficient light trapping design, the ration of nanowire diameter and periodicity should exceed 0.5 for the optimized solar spectral absorption [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Chakthranont et al used so-called black silicon which shows a very high light absorption and is composed of needle-shaped (tapered) nanowires, in their case ~3 μm length, ~200 nm average diameter and ~300 nm spacing. We assume that the microwires in our system do absorb more light than flat equivalents as proven by Elbersen et al [46,47] and Kelzenberg et al [25] but believe that mass transfer overcompensates this effect and leads to an overall underperformance of the microwire structures compared to flat samples. In contrast, the positive light trapping effect of microwires overcompensated the negative diffusion effect in the system reported by Chakthranont et al as these authors used smaller microwire dimensions leading to a significantly shorter ion diffusion path length.…”
Section: Light Absorption Propertiesmentioning
confidence: 99%
“…[25,46] For instance, Elbersen et al have studied the effects of microwire length on photovoltaic activity of silicon microwires with radial p/n junctions and a spacing of 2 µm and found that all tested microwires with a length between 10 µm and 60 µm outperformed flat equivalents under perpendicularly oriented illumination. [47] However, Boettcher et al prepared similarly sized microwire arrays with a radial n + /p junction, deposited platinum on the tops and tested them for photocatalytic hydrogen evolution. [48] They found that the efficiencies of silicon microwire photocathodes were 5.8% and that of planar control samples 9.6%.…”
Section: Light Absorption Propertiesmentioning
confidence: 99%